In situ monitoring and 3D geomechanical numerical modelling to evaluate seismic and aseismic rock deformation in response to deep mining. (May 2020) - De Santis, Francesca; Renaud, Vincent; Gunzburger, Yann; Kinscher, Jannes; Bernard, Pascal; Contrucci, Isabelle
Abstract: In this work we investigated seismic and aseismic rock mass behaviors in response to deep underground mining. For this purpose, an area under production of the metal mine of Garpenberg (Sweden) was instrumented with a geophysical and geotechnical monitoring network. In situ monitoring data were analyzed and interpreted considering mining operations and the local geological setting. In addition, a 3D elasto-plastic numerical model was built to better understand the interactions between quasi-static stress changes due to mining and the generation of the induced seismicity. Results of this multiparameter approach show a complex rock mass response. We observed two main types of seismic behaviors: one local and temporally short, directly induced by production, the other long-lasting over time and remote from excavations being mainly controlled by geological heterogeneities. In addition to seismicity, we also observed creep-like phenomena induced by mining. In turn, these time-dependent strains appear to be a third mechanism driving seismicity. All these findings underline the importance of considering both seismic and aseismic deformations when one wants to characterize the rock mass response to mining. This significantly enhances our understanding of the phenomena involved, as well as their interactions, for an improved hazard assessment in deep mining operations.